Risk factors for the rupture of intracranial aneurysms: a systematic review and meta-analysis - Ma, Jinyuan; Zheng, Yuehua; Li, Puxian; Zhou, Tao; Sun, Zhen; Ju, Tongze; Li, Aijun (Frontiers in Neurology, 2023)
Purpose The study aimed to identify potential risk factors for aneurysm rupture by performing a systematic review and meta-analysis. Materials and methods We systematically searched the PubMed, Embase, and Cochrane Library electronic databases for eligible studies from their inception until June 2023. Results Eighteen studies involving 17,069 patients with unruptured intracranial aneurysm (UIA) and 2,699 aneurysm ruptures were selected for the meta-analysis. Hyperlipidemia [odds ratio (OR): 0.47; 95% confidence interval (CI): 0.39–0.56; p < 0.001] and a family history of subarachnoid hemorrhage (SAH) (OR: 0.81; 95% CI: 0.71–0.91; p = 0.001) were associated with a reduced risk of aneurysm rupture. In contrast, a large-size aneurysm (OR: 4.49; 95% CI: 2.46–8.17; p < 0.001), ACA (OR: 3.34; 95% CI: 1.94–5.76; p < 0.001), MCA (OR: 2.16; 95% CI: 1.73–2.69; p < 0.001), and VABA (OR: 2.20; 95% CI: 1.24–3.91; p = 0.007) were associated with an increased risk of aneurysm rupture. Furthermore, the risk of aneurysm rupture was not affected by age, sex, current smoking, hypertension, diabetes mellitus, a history of SAH, and multiple aneurysms. Conclusion This study identified the predictors of aneurysm rupture in patients with UIAs, including hyperlipidemia, a family history of SAH, a large-size aneurysm, ACA, MCA, and VABA; patients at high risk for aneurysm rupture should be carefully monitored. Systematic Review Registration Our study was registered in the INPLASY platform (INPLASY202360062).